Reading for The Future: Literacy Movement at SB Wira Damai Selangor, Malaysia - Lasmiatun, KMT; Istifaroh, Siti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The Wira Damai Learning Studio in Selangor, Malaysia, is a non-formal educational institution that focuses on basic literacy for the children of Indonesian migrant workers. Through literacy-math teaching (calistung) activities and social skills development, the program aims to provide basic education for children who have difficulty accessing formal schools. With the support of volunteer teaching staff and KKN students, this activity also introduces children to relevant social values and life skills. The results showed a significant increase in children's basic literacy skills and selfconfidence. This article highlights the importance of this program as an educational model for the migrant community in Malaysia.